2021
DOI: 10.1002/ijop.12787
|View full text |Cite
|
Sign up to set email alerts
|

Depression and social anxiety mediate the relationship between parenting styles and risk of eating disorders: A study among Arab adolescents

Abstract: I n multicultural Israel, the prevalence of eating disorders (EDs), a common chronic disorder among Western adolescents (especially females), has risen for Arab adolescents, who belong to an Eastern collectivist society. The study examines family and psychological factors that may increase the risk of EDs among Muslim Arab adolescents. We expected social anxiety and depressive symptoms to mediate the association between parenting styles and risk of EDs, with possible gender differences in the mediation model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
8
0
6
Order By: Relevance
“…Nonetheless, self-reported questionnaires were proven to be valid and applied worldwide. Third, although a number of potential confounders were included, there are some unmeasured confounders (e.g., parenting styles, substance use and other variables) that may contribute to these associations ( 63 , 64 ). Forth, the current study only includes college students who are currently on campus and did not account for those absent.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, self-reported questionnaires were proven to be valid and applied worldwide. Third, although a number of potential confounders were included, there are some unmeasured confounders (e.g., parenting styles, substance use and other variables) that may contribute to these associations ( 63 , 64 ). Forth, the current study only includes college students who are currently on campus and did not account for those absent.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a systematic review of recent research has demonstrated that parenting styles ( e.g ., authoritative, authoritarian, and permissive parenting styles) have been weakly to moderately associated with individual domains of child feeding, wherein permissive parenting style was negatively associated with monitoring for both fathers and mothers (as the most consistent relationship) ( Collins, Duncanson & Burrows, 2014 ). According to these phenomenological descriptions, the FED model suggests that disturbed EAB can be considered one of the most important manifestations of unhealthy parenting and maladaptive coping styles—a hypothesis supported by recent evidence in several studies ( Waller, Kennerley & Ohanian, 2007 ; Haycraft & Blissett, 2010 ; Enten & Golan, 2009 ; Zubatsky, Berge & Neumark-Sztainer, 2015 ; Peleg, Tzischinsky & Spivak-Lavi, 2021 ; Collins, Duncanson & Burrows, 2014 ). In detail, for detached protector/self-soother modes, compensatory and restrictive eating behaviors can act as a form of primary or secondary emotional avoidance while producing soothing feelings of numbness, or euphoria in some cases ( Brown et al, 2016 ).…”
Section: Introductionmentioning
confidence: 84%
“…Women reported higher levels of emotional reactivity + fusion with others than men, as was found in previous studies [ 47 ]. This may be due to overly high expectations that they function as spouses, mothers and career wives [ 20 ]. Furthermore, due to higher levels of oxytocin, estrogen and progesterone, women tend to be more sensitive and emotional than men [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that Arabs would report lower levels of emotional cutoff (DoS) and higher levels of anxiety and depressive symptoms (emotional distress) than Jews (Hypothesis 2). Based on documented gender-related findings on DoS and emotional distress [20], we also predicted (Hypothesis 3) that women would report higher levels of emotional reactivity and fusion with others (DoS), as well as anxiety and depressive symptoms (emotional distress), than men. Finally (Hypothesis 4), we assumed that DoS would be associated with emotional distress, high levels of emotional reactivity, emotional cutoff and fusion with others and a low level of I-position would be associated with high levels of stress and depressive symptoms.…”
Section: Research Objectives and Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation